Dampak Lalu Lintas Akibat Pengoperasian BRT Trans Semarang Koridor IV Terminal Cangkiran - Semarang Tawang - Bastian Tri Noviadi; Widjonarko Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2018)
The rapid physical growth of Semarang City also boost the activity of transportation. The increase of transportation activity can be seen from the increase of vehicle per year. This is not offset by the increase in road length which result in the increase of traffic jam potential. According to the Ministry of City Transportation, the avarage road level of service is at C which is below he standard quality. As an attempt to resolve the problem of transportation, the government of Semarang City preparing a mass transportation service in form of BRT. The goal of this study is to analysis possible impact of traffic from the operation of BRT Trans Semarang in Corridor IV Cangkiran - Semarang Tawang. The method of analysis used in this study is quantitative descriptive. Primary data in the form of vehicle volume is done by traffic counting while the secondary data is collected from Ministry of Transportation, previous studies, and internet. Based on the analysis, it is indicated that Trans Semarang have significant influence on the traffic. It is indicated that the road performance on two bus stop which is Jrakah Market and Semarang District court is reduced while there is an increase of performance on the other five bus stop. From the seven bus stop investigated, only three bus stop successful in attempt to reduce the traffic jam by reducing the degree of saturation to below 0.75.The three bus stop in question are Cangkiran Terminal, Gas Station Semarang New Hill, and Tawang Station. When Trans Semarang operate at the start of the year, there is an increase in road performance. However the traffic load keep increasing every year because of the increase in private vehicle and the resident reluctant to switch to BRT. The result of study are recommendation to handle traffic in the form of building a private lane in arterial road, widen the road, build small lane on bus stop to reduce side friction, and sanction for those who park in beside the road.